2011
DOI: 10.1016/j.neurobiolaging.2011.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of aging

Abstract: Human longevity and healthy aging show moderate heritability (20–50%). We conducted a meta-analysis of genome-wide association studies from nine studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium for two outcomes: a) all-cause mortality and b) survival free of major disease or death. No single nucleotide polymorphism (SNP) was a genome-wide significant predictor of either outcome (p < 5 × 10−8). We found fourteen independent SNPs that predicted risk of death, and eight SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 74 publications
5
112
0
1
Order By: Relevance
“…However, these may provide starting points for future explorations of aging biology. Notably, genetic variation at the related gene GRIA1 was robustly associated with longevity in a genome-wide association study meta-analysis (55). Several other genes identified by Bell et al were members of gene families represented among our top findings.…”
Section: Consistency Of Specific Findings With Previous Studiesmentioning
confidence: 57%
“…However, these may provide starting points for future explorations of aging biology. Notably, genetic variation at the related gene GRIA1 was robustly associated with longevity in a genome-wide association study meta-analysis (55). Several other genes identified by Bell et al were members of gene families represented among our top findings.…”
Section: Consistency Of Specific Findings With Previous Studiesmentioning
confidence: 57%
“…Thus, the intensity and efficacy of clearance of the damaged molecules largely determines the progression of neurodegenerative disorders [100][101][102] but also the pace of brain ageing in healthy individuals [46,103,104]. The significance of autophagic processes in normal ageing is shown by a genome-wide association study which found a significant association between genetic variance in autophagy associated genes and survival in healthy aged humans [105]. It is generally observed that improving clearance with the induction of autophagy [10,106] or proteasome activity [107,108] slows down the ageing process and improves cognitive functions.…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%
“…In some instances, single gene mutants have been observed to increase maximum life span by as much as 40% (3). Other studies have focused on identifying genes that are associated with longevity in humans-that is, genes observed to have a higher allele frequency in centenarians (4)(5)(6). However, such human longevity-associated genes (LAGs) seem to be very rare, and although a few have been confirmed in independent studies (2,3), their existence remains controversial.…”
mentioning
confidence: 99%